The Genre Sonnet in the Poesis of Shakespeare - kizi, Qayumova Nigora Muxtor (Researchparks Publishing, 2023)
The sonnet is one of the decorative patterns of Western poetry, and in the 16th century, a new variation of the sonnet appeared in England. Shakespeare produced quality work in this form, which evolved from Italian poetry to English poetry. William Shakespeare, a notable example of Renaissance literature, wrote 154 sonnets that contributed to the development of the sonnet form in English literature. Shakespeare's sonnets hold a unique position in the canon of sonnets because of their exceptional aesthetic value. The article outlines the sonnet writer's proficiency in the implementation of literary devices.